Development, Optimization, and Clinical Relevance of Lactoferrin Delivery Systems: A Focus on Ocular Delivery - Erika Ponzini; Gloria Astolfi; Rita Grandori; Silvia Tavazzi; Piera Versura (MDPI AG, 2024)
Lactoferrin (Lf), a multifunctional protein found abundantly in secretions, including tears, plays a crucial role in ocular health through its antimicrobial, immunoregulatory, anti-inflammatory, and antioxidant activities. Advanced delivery systems are desirable to fully leverage its therapeutic potential in treating ocular diseases. The process of Lf quantification for diagnostic purposes underscores the importance of developing reliable, cost-effective detection methods, ranging from conventional techniques to advanced nano-based sensors. Despite the ease and non-invasiveness of topical administration for ocular surface diseases, challenges such as rapid drug elimination necessitate innovations, such as Lf-loaded contact lenses and biodegradable polymeric nanocapsules, to enhance drug stability and bioavailability. Furthermore, overcoming ocular barriers for the treatment of posterior segment disease calls for nano-formulations. The scope of this review is to underline the advancements in nanotechnology-based Lf delivery methods, emphasizing the pivotal role of multidisciplinary approaches and cross-field strategies in improving ocular drug delivery and achieving better therapeutic outcomes for a wide spectrum of eye conditions.